1998
DOI: 10.1002/(sici)1097-0185(199807)251:3<406::aid-ar17>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of human scalp hair shafts as revealed by freeze-substitution fixation

Abstract: Human scalp hair is important as a diagnostic clue to many diseases, in medical jurisprudential investigations, and also as a subject of cosmetic treatments. While many ultrastructural studies of the human hair root including the hair follicle have been reported, few studies have been done on the human hair shaft. We report here the ultrastructure of human scalp hair shafts prepared by a rapid-freezing technique followed by freeze-substitution fixation that allows the observation of fine cell structures. Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 20 publications
1
15
1
Order By: Relevance
“…The cuticle CMC and the cortex CMC showed a slightly lower electronic density than the structures around them. In the white hair samples, melanin granules were very few or non existent, but the rest of their structures were basically the same as those of black hair 6) .…”
Section: A Morphological Observation Of the Cuticle And Cortexmentioning
confidence: 83%
See 1 more Smart Citation
“…The cuticle CMC and the cortex CMC showed a slightly lower electronic density than the structures around them. In the white hair samples, melanin granules were very few or non existent, but the rest of their structures were basically the same as those of black hair 6) .…”
Section: A Morphological Observation Of the Cuticle And Cortexmentioning
confidence: 83%
“…The electronic density of the A-layer is increased but that of the endocuticle is decreased with cold permanent wave treatment, which contains thioglycolic acid as a reducing ingredient, and it is thought that OsO 4 reacts with the cleaved disulfide bond of cystine through the action of the reducing agent 6) . On the other hand, in the Os+Es images of this study, the electronic density of both A-layer and endocuticle was increased in the bleached hair ( Fig.…”
Section: A Change Of the Electronic Density Caused By Bleach Relatinmentioning
confidence: 99%
“…However, treatment with ATG or 2-mercaptoethanol in phosphate buffer has been used to observe the fibrillar structure in the cortex. In addition, the A-layer in hair cuticle cells is also stained [6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have introduced a rapidfreezing technique followed by a freeze-substitution fixation in the ultrastructural study of the human scalp hair shaft and have shown excellent ultrastructures in a form close to those in the living state [25]. Thus, we have employed the rapid-freezing technique in order to study the immunoelectron microscopic distribution of hair keratins in the hair shafts.…”
Section: Discussionmentioning
confidence: 99%
“…One reason for that is that the technical complication due to poor penetration of chemical reagents (i.e., chemical fixatives, dehydration alcohol and embedding media) into the dry tissue during preparation for transmission electron microscopy (TEM) analysis. Recently, we have overcome this obstacle by applying a rapid-freezing and subsequent freeze-substitution fixation technique to the ultrastructural study of the human scalp hair shaft and have revealed its fine inside view by TEM [25]. It would be interesting to show in situ subcellular distribution and differential expression of hair components on the fine structure of human hair as revealed by the rapidfreezing technique.…”
Section: Introductionmentioning
confidence: 99%